ANALYSIS OF SWOT, IFAS, EFAS, AND BLC IN THE HEAVY EQUIPMENT INDUSTRY IN BALI - Mandira, I Made Chandra; Damayanti, Gusti Agung Ayu Putu Cahya (Fakultas Ekonomi, Universitas Negeri Jakarta, 2023)
This research aims to develop marketing strategies that can be applied to the heavy equipment rental company CV Dana Karya in order to withstand competition from similar competitors. The research method utilizes a mixed-method approach with an exploratory research approach. Data collection techniques are carried out through interviews, questionnaires, and documentation, which are tested using triangulation techniques. Informants were obtained through purposive sampling techniques, involving 7 individuals including company owners, employees, and customers. This study is analyzed using the SWOT analysis technique with weights, ratings in the calculation of IFAS and EFAS, which are then analyzed with the business life cycle. The results of this research indicate that the company's position obtained from the total scores of IFAS and EFAS is in quadrant 1, by implementing a growth-oriented strategy focused on SO (strength-opportunities) strategies, utilizing all internal strengths of the company to seize and make the most of external opportunities. Based on the classification of internal-external factors, an IE matrix is obtained, which is located in cell 1 indicating that CV Dana Karya is in a growth and build position. In relation to the business life cycle, it can be determined that the current position of CV Dana Karya's heavy equipment rental business is in the growth phase.